REMOVAL OF ARSENIC FROM AQUEOUS SOLUTION BY PHOTOCATALYTIC UV IRRADIATION - Mahsa Jahangiri-rad (European Scientific Journal, ESJ, 2014)
The purpose of this research was to investigate the photocatalytic removal of arsenic from aqueous solution using UV/TiO2 process in a batch system. A 120 W UV lamp with irradiation 247 nm wave lenght inside a quartz jacket was submerged in the reactor to provide better irradiation of water samples in the presence of TiO2 nanoparticles. The optimum dosage of TiO2 was obtained equal to 1 g/L, with variation TiO2 dosage at constant pH and initial concentrations of arsenic. The effect of pH, contact time and initial concentration of arsenic was studied at the constant amount of TiO2(1g/L). The results showed that photocatalytic removal efficiency increased with increasing reaction time and TiO2 dosage. In addition, it was found that removal efficiency of arsenic decreased by increasing initial arsenic concentration and pH. In conclusion the results showed that UV/TiO2was an effective method in removal of arsenic from aqueous solutions.